Axial and flexural behavior of unreinforced and FRP bar reinforced circular concrete filled FRP tube columns. (30th September 2016) - Hadi, Muhammad N.S.; Khan, Qasim S.; Sheikh, M. Neaz
Highlights: 16 CFFT and 4 steel RC specimens are tested under concentric and eccentric axial loads and flexural load. Failure modes and load deformation behavior of tested specimens are reported. Effect of eccentricity on the axial load and ductility of CFFT specimens is investigated. Effect of four point loads on the flexural load and ductility of CFFT is investigated. Experimental axial load bending moment interaction curves are presented. Abstract: Fiber Reinforced Polymer (FRP) composites have emerged as a viable alternative of steel reinforcement due to higher ultimate tensile strength to weight ratio and corrosion resistance of FRP composites. Concrete Filled Fiber Reinforced Polymer Tube (CFFT) technique for new column construction has attracted significant research attention. This paper investigated the axial and flexural behavior of Concrete Filled Carbon FRP Tube (CFRP CFFT) columns with and without CFRP bar and concrete filled Glass FRP (GFRP) tube columns with and without GFRP bar. The test results of 16 circular CFFT and four steel Reinforced Concrete (RC) specimens of 203–205 mm diameter and 800–812 mm height have been reported in this paper. The test results showed a larger reduction in the confinement effectiveness of FRP tube than steel helices under increasing applied load eccentricity. FRP bar reinforced CFFT specimens exhibited higher axial loads, flexural loads, and deformations at peak loads than unreinforced CFFT and steel RC specimens. Experimental axial load-bending moment interaction curves of tested specimens also showed the improved performance of FRP bar reinforced CFFT specimens.